Factors Affecting the Occurrence of Diabetic Ulceration in Patients with Type II Diabetes Mellitus - Reeny Purnamasari; Febie Irsandy Syahruddin; A. Millaty Dirgahayu (UMI Medical Journal, 2025)
Background: Diabetes mellitus (DM) is a condition characterized by high blood glucose levels, which increases the risk of macrovascular and microvascular complications, thereby reducing patients' quality of life. One complication of DM is neuropathy, which is characterized by reduced sensation in the feet and is often associated with foot ulcers. Approximately 50% of the diabetic population is at risk of developing diabetic foot ulcers.  Objective: This study aimed to identify factors associated with the occurrence of diabetic foot ulcers in patients with type II diabetes mellitus. Methods: This study used a descriptive-analytic design with a cross-sectional approach. Results: The study found that diabetic foot ulcers in patients with type 2 DM were most prevalent in those over the age of 65 (25 individuals, 75.76%), female (19 individuals, 57.6%), with a normal Body Mass Index (BMI) (24 individuals, 72.73%), having suffered from type 2 DM for more than five years (26 individuals, 78.79%), high HbA1c levels (30 individuals, 90.91%), and regular foot care practices (22 individuals, 66.67%). Conclusion: The most dominant factors associated with diabetic foot ulcers are older age (> 65 years), duration of diabetes of more than five years, high random blood glucose levels, and elevated HbA1c levels.